STRUCTURAL AND FUNCTIONAL STATE OF LIVER AND PANCREAS IN CHILDREN WITH REACTIVE ARTHRITIS - Yanovska, K.O. (World of Medicine and Biology, 2013)
It was defined clinical and laboratory characteristics of the pancreas and liver in children with reactive arthritis. The children were divided by age, divided into three age groups. It was assessed complaints physical examination findings, blood chemistry, ultrasound, coprogram. Ultrasound examination of the abdomen was carried out on an empty stomach and with a load of food to determine the functional state of the pancreas. Adverse criteria were developed, which proved possible functional pancreas and liver disorders in children with reactive arthritis.
Keywords: reactive arthritis; children; pancreas; liver